THE INFLUENCE OF LEADER BEHAVIORS AND PSYCHOLOGICAL SAFETY ON ORGANIZATIONAL LEARNING FROM FAILURES: AN EMPIRICAL RESEARCH - Nguyen, Thi Thi Nga (2014)
It is well acknowledged that failure contains within it valuable information and organizational learning from failure is crucial for an organization’s innovation, performance and adaptability. Process of learning often relies on interactions between people to decide what need to be improved and how to do it. The current research addresses the question of how leader behaviors and psychological safety facilitates organizational learning from failures. Qualitative data collected from nineteen participants show that organizational learning from failure varies significantly across different departments in the same organization. Findings of the current research shed light on the importance of leader behaviors and psychological safety in the working place on cultivating the organizational learning from failures.